2015
DOI: 10.1080/17461391.2015.1013995
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder prevention initiatives for athletes: A review

Abstract: A substantial amount of evidence suggests that collegiate and elite athletes involved in weight-sensitive sports are at greater risk of developing eating disorders (EDs) than the general population. With the limited effectiveness of treatment for EDs, prevention of EDs has been broadly considered in the literature. The present paper reviewed the existing literature on ED prevention programmes for athletes in order to determine the current status of prevention programmes and recommend future directions. The ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 79 publications
0
47
0
1
Order By: Relevance
“…Effective eating disorder prevention programmes should be multimodal, interactive and target athletes and coaching staff 161. One successful intervention is a peer-led educational programme for female athletes that resulted in improved bulimic pathology 1 year postintervention 162.…”
Section: Prevention Of Relative Energy Deficiency In Sportmentioning
confidence: 99%
“…Effective eating disorder prevention programmes should be multimodal, interactive and target athletes and coaching staff 161. One successful intervention is a peer-led educational programme for female athletes that resulted in improved bulimic pathology 1 year postintervention 162.…”
Section: Prevention Of Relative Energy Deficiency In Sportmentioning
confidence: 99%
“…As noted by Bar and colleagues (Bar et al, ), larger trials with longer follow‐ups are needed for programs that demonstrate positive results. The aim of the present RCT was to replicate and extend the preliminary results from the pilot/feasibility study conducted by Becker et al () using a larger sample and a longer follow‐up.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, most FA ED prevention (or risk factor reduction) programs have shown limited effects on empirically supported ED risk factors (Bar, Cassin, & Dionne, 2016). Yet, two programs (Becker, McDaniel, Bull, Powell, & McIntyre, 2012;Martinsen et al, 2014) have produced long-term effects in ED symptoms or risk factors with FAs.…”
mentioning
confidence: 99%
“…However, the incidence of eating disorder onset was not reduced (Coelho et al, ). In another review of athlete eating disorder prevention programmes ( n = 11; Bar, Cassin, & Dionne, ), it was reported that most interventions demonstrated promising findings in preventing or reducing eating psychopathology in athletes, with four studies reporting sustained intervention effects [2–6 weeks ( n = 2); 9–36 months ( n = 2)]. Additionally, the most effective programmes were identified as those that included multiple intervention targets (e.g., athletes, coaches, and parents) and those conducted with athletes under 18 years (Bar et al, ).…”
Section: Introductionmentioning
confidence: 99%